Digital Music Terminology and Lexical Gaps in Indonesian: Linguistic Adaptation and Register Formation in the Era of Digital Audio Production - Etti Suharti; Soni Reffali (PESHUM : Jurnal Pendidikan, Sosial dan Humaniora, 2026)
This study examines how English‑origin digital music terminology is adopted, adapted, and integrated into Indonesian professional discourse, with a focus on lexical gaps, phonological adaptation, and morphological hybridization. The research adopts a qualitative descriptive design, analyzing thirty English technical terms drawn from Indonesian‑language YouTube tutorials, online discussion forums (IMDC and Music Indonesia), educational workshops in digital music production, and the terminology embedded in digital audio workstation (DAW) interfaces. Data were collected from materials published between 2022 and 2027 and analyzed through a coding schema that classified terms by semantic function, degree of phonological adaptation, and morphological status (direct borrowing, phonologically adapted loan, or morphologically hybridized form). The findings reveal that most terms function as necessary loans, used because Indonesian lacks precise equivalents for concepts such as mixing, mastering, plugin, gain, and latency; many of these terms appear in their original English form or with partial phonological adaptation, while others combine with Indonesian affixes (e.g., ngemix, dimastering, diplugin) to form hybrid verbs. The study concludes that global digital audio production terminology is not merely borrowed but increasingly anchored in Indonesian grammar, giving rise to a specialized professional register that reflects the dynamic interplay between technological globalization and localized linguistic adaptation